Internal Control Systems and Financial Accountability of Local Governments in Uganda. A Case study of Iganga District, Uganda. - Kongola , Dauda; Bakashaba , Edmand (Student’s Journal of Health Research Africa, 2022)
Background This study investigated the relationship between the internal control systems and financial accountability of local governments in Ugandan a case study of the district by examining the relationship between control environment and financial accountability; control activities and financial accountability and assessing the relationship between Information and communication and financial accountability in district local government. Methodology The researcher used a questionnaire to collect data from the field and used the SPSS data analysis package version 2022, Pearson correlation to determine the relationship between the variables under investigation. Results: The findings revealed a strong relationship between control activities and financial accountability with dimensions such as expenditures and disbursements requests backed by appropriate supporting documents, approval of expenditures, and cash releases by authorized persons, Bank reconciliations reviewed by an officer independent of those processing cash, and payments, clear separation of roles and responsibilities, Budget reviews, presence of a system that identifies and safeguards Institutional Assets more findings found a significant relationship between information and communication with generating relevant quality information to support the functioning of internal control if employs freely discuss internal control matters with those charged with governance and if organization reviews the received information from external parties and responds appropriately as the major constructs for promotion of financial accountability. Conclusion: There is a significant relationship between the internal control environment and financial accountability as reflected by the Pearson correlation; significant at the 0.01 level (2-tailed.) Recommendation: Local governments must invest more effort in the accounting and financial management system, and management must continuously and effectively be committed to the accounting system which will enrich financial accountability.